“Eco School Project” Program to Create an Environmentally Friendly School Garden at UPTD SDN Cinini Sumbermulya Village Indramayu - Yusrina Nafilah; Idah Hamidah; Eva Yuliana (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
Climate change and environmental degradation are increasingly urgent global issues to address. Global warming, air pollution, deforestation, and various other forms of environmental damage threaten the sustainability of life on earth. In facing these challenges, education plays a key role in shaping pro-environmental awareness and behavior among the younger generation. Schools as educational institutions have a great responsibility in instilling environmental values ​​in students. One relevant initiative in the context of environmental education is the